Structural equation modelling of reality TV shows in the Philippines vis a vis people’s phenomenological views - RENAN P. LIMJUCO; FELIX C. CHAVEZ JR; LIEZL A. LOGUINSA; JOSEPH ELMER G. NOVAL (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This research aimed to verify a hypothesized model describing the assumed nature of reality TV shows in the Philippines by examining latent constructs like the concepts of artistry, potential commercial value, and merit evaluation. This research, which used a mixed-methods methodology, also sought to characterize and comprehend the participants’ perspectives on the multifaceted character of reality TV in the country.Methodology: Purposive sampling was used to select 422 participants from Davao City’s educational institutions. We used a custom-made 5-point Likert questionnaire with 47 questions for this survey. Meanwhile, a focus group consisting of eight people was assembled (FGD).Findings: The results showed that the criteria used in reality TV shows are largely responsible for defining the concept of artistry, although the judges’ credibility is still an important consideration. The contestant’s marketability is heavily influenced by his character. Viewers’ approval and the television networks’ preference are both important factors in determining quality.Novelty/Implications: This research examined the best-fit model of merit evaluation and phenomenological perspectives on Philippine reality television, highlighting the genre’s high levels of concept of artistry, commercial value, and merit evaluation.